KONFLIK PSIKOLOGI TOKOH UTAMA SUBARU MIYAMOTO DALAM MANGA SUBARU KARYA SODA MASAHITO - Nonik Wiratih, Ni Luh (Humanis, 2015)
Psychological conflict is psychological situation when someone experienced two or more motives that contradicted one with another. Psychological conflict can be found in situation where need, hope, wish, and aim are different and contradicted each other at the same time and caused unpleasant feeling. Psychological conflict can also be found in manga, one of them is in Subaru. The psychological conflict in this manga were analyzed based on theory of psychoanalytic and supported with theory of semiotic and theory of drawing a comic. The result shows that there are five forms of psychological conflicts that Subaru have experience such as feeling guilty over the death of Kazuma, confusion of choosing between ballet or education, Subaru vacillation when perfoming on stage for the first time, feeling guilty over the death of Izusu aunt, and Subaru vacillation between back to Japan or leave Japan. The efforts of Subaru to overcome his psychological conflicts are making Kazuma death as a motivation to continue ballet, decided to live as ballerina, convincing herself to be brave to dance on stage, motivated herself to win Lausanne contest after the Izusu death, and decided to leave Japan.
Keywords: Psychoanalytic, Semiotics, Psychological conflict